Non-Muslim Perspectives on Food Products Labeled with the Halal Logo - Fadhillaah, Hanif (Journal of Halal Research, Policy, and Industry, 2022)
This research was aimed to examine empirically about Non Muslim Perspective to Choosen Halal Labeled Food. This analysis used a Dependent Variable is Choosen Halal Labeled Food. The Independent Variable of Non Muslim Perspective. This type of research is Cualitative Research with Descriptive Analysis. The sample of this research are Non Muslim Community a total of 73 respondents. The sample was conducted by Purposive Sampling Method. Collecting data was conducted by a questionnaire distributed via Google Form to respondents. The result of this research showed that Non Muslim Society that are male and female (72,2% of male and 27,8% of female) think positively and more significantly agreed with Halal Labeled in Food Product. The Halal Labeled can provide benefits for consument or producer from commercil institute. Because Halal Product can give health guaranteed and proof of Food Savety.